Analysis of Achievement of Developmental Tasks of Grade IV Elementary School Students in the Digital Era - Zalsa, Trinanda; Merliana, Anggit (Jurnal Riset Ilmu Pendidikan, 2025)
The purpose of this study is to see the level of achievement of students' developmental tasks in order to be used as a reference in knowing the development that occurs in students, especially in the digital era. The approach used is a qualitative approach using a descriptive method. The population of the study was 23 fourth grade students at an Elementary School in Tasikmalaya Regency. The technique used was a saturated sampling technique, namely all members of the population were used as samples. The instrument for collecting data on the achievement of developmental tasks was the Developmental Task Inventory (ITP) with the help of Developmental Task Analysis (ATP) software as software that makes it easy to process ITP quickly and efficiently. The results of this study indicate that the level of student development is at the self-protection level with an average development level of 2.85, a standard deviation of 0.19, and a coefficient of variance of 6.76%. Based on these results, special attention and assistance are needed for students so that students achieve ideal development, namely at the level of self-aware development.